Meningkatkan kemampuan membaca permulaan dengan pendekatan quantum learning berbantuan aplikasi Canva pada siswa kelas II - Popong Hoerun Nisa; Ryan Dwi Puspita; Yeni Hadianti (COLLASE (Creative of Learning Students Elementary Education), 2024)
This study aimed to investigate the effectiveness of the quantum learning model assisted by Canva application in improving the early reading skills of grade 2 students. The use of this model was based on the problem of low motivation, interest, and less engaging learning activities. This research employed a quantitative descriptive method with a one-group pretest-posttest design. The sample consisted of 22 grade 2 students at SDN Cibeber 3, Cimahi City. Data analysis was conducted using a paired sample t-test, normalized gain (N-Gain) test, and a questionnaire to assess students' responses after following this learning model. The results showed that: 1) There was a significant increase in students' early reading skills after following the quantum learning model assisted by Canva application; 2) The N-gain score of 0.46 or 46% was categorized as less than effective; 3) Further development and efforts are needed to improve the effectiveness of using the quantum learning model; and 4) The results of the student questionnaire indicated that the illustrations on the learning texts helped students become more enthusiastic during the learning process.